2018
DOI: 10.1111/mmi.13897
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid deprivation and central carbon metabolism regulate the production of outer membrane vesicles and tubes by Francisella

Abstract: Francisella tularensis is a highly virulent Gram-negative bacterial pathogen that causes the zoonotic disease tularemia. F. novicida, a model tularemia strain, produces spherical outer membrane vesicles (OMV), as well as novel tubular vesicles and extensions of the cell surface. These OMV and tubes (OMV/T) are produced in a regulated manner and contain known virulence factors. Mechanisms by which bacterial vesicles are produced and regulated are not well understood. We performed a genetic screen in F. novicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 77 publications
1
30
1
1
Order By: Relevance
“…Although these authors discussed that OMT formation was caused by cell stress they did not explore the possibility that some cells were dying 8 . Finally, OMTs were also found in the pathogens Francisella novidica and Francisella tularensis where OMTs were stimulated by stress conditions induced by amino-acid deprivation or during macrophage infection 49 , 50 . Nevertheless, these structures, being formed from the outer membrane, do not have to cross the cell wall and, therefore, the mechanism of their formation is likely different from that one of B. subtilis NTs.…”
Section: Discussionmentioning
confidence: 99%
“…Although these authors discussed that OMT formation was caused by cell stress they did not explore the possibility that some cells were dying 8 . Finally, OMTs were also found in the pathogens Francisella novidica and Francisella tularensis where OMTs were stimulated by stress conditions induced by amino-acid deprivation or during macrophage infection 49 , 50 . Nevertheless, these structures, being formed from the outer membrane, do not have to cross the cell wall and, therefore, the mechanism of their formation is likely different from that one of B. subtilis NTs.…”
Section: Discussionmentioning
confidence: 99%
“…These studies further suggest at the vaccine potential of a Fn slt mutant that overproduces OMTs able to elicit an effective immune response. A more recent study found that production of OMTs was triggered by cysteine deprivation in rich medium, indicating a role for OMTs in metabolism as well as in virulence (Sampath et al, 2018). Interestingly, F. novicida transposon mutants exhibiting hyper-vesiculation had interruptions in genes involved in cell division and peptidoglycan modification, such as ftsK and carboxypeptidases like dacD .…”
Section: Discussionmentioning
confidence: 99%
“…Production of OMV has previously been described in F. novicida (McCaig et al, 2013) and F. tularensis subsp. tularensis SchuS4 (Sampath et al, 2017) and a novel and unusual nanotubular shape was observed. Similar structures were also found in F. noatunensis , a related fish pathogen (Brudal et al, 2015).…”
Section: Introductionmentioning
confidence: 98%